Approximate value of Coinage of U.S. in Gold and Silver from the beginning in 1792 to 30th June, 1882 - Booth, James Curtis (1882)
Calculations written on U.S. Mint letterhead, approximating the value of gold and silver coinage of the United States.
Keywords: Gold; Smelting; Coinage; Silver; Metals--Refining; Mint of the United States; Metallurgy; Silver--Refining; Gold--Refining; Booth, James Curtis, 1810-1888; Precious metals; United States Mint